Striving to Be 'Clearly Open' and 'Crystal Clear' : Monetary Policy Communication of the CNB - Bulir, Ales.; Smidkova, Katerina (Washington, D.C. : International Monetary Fund, 2008)
The Czech National Bank has a respectable track record in terms of its policy actions and the corresponding inflation outturns. Using a simple forward-looking policy rule, we find that its main communication tools-inflation targets, inflation forecasts, verbal assessments of the inflation risks contained in quarterly inflation reports, and the voting within the CNB Board-provided a clear message in about three out of every four observations in our 2001- 2005 sample.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet